Current advances in the novel functions of hypoxia‐inducible factor and prolyl hydroxylase in invertebrates. Issue 6 (20th September 2015) - Wang, L.; Cui, S.; Ma, L.; Kong, L.; Geng, X.
Abstract: Oxygen is essential for aerobic life, and hypoxia has very severe consequences. Organisms need to overcome low oxygen levels to maintain biological functions during normal development and in disease states. The mechanism underlying the hypoxic response has been widely investigated in model animals such as Drosophila melanogaster and Caenorhabditis elegans . Hypoxia‐inducible factor (HIF), a key gene product in the response to oxygen deprivation, is primarily regulated by prolyl hydroxylase domain enzymes (PHDs). However, recent findings have uncovered novel HIF‐independent functions of PHDs. This review provides an overview of how invertebrates are able to sustain hypoxic damages, and highlights some recent discoveries in the regulation of cellular signalling by PHDs. Given that some core genes and major pathways are evolutionarily conserved, these research findings could provide insight into oxygen‐sensitive signalling in mammals, and have biomedical implications for human diseases.